2010
DOI: 10.1371/journal.pone.0011616
|View full text |Cite
|
Sign up to set email alerts
|

Genome Wide Linkage Study, Using a 250K SNP Map, of Plasmodium falciparum Infection and Mild Malaria Attack in a Senegalese Population

Abstract: Multiple factors are involved in the variability of host's response to P. falciparum infection, like the intensity and seasonality of malaria transmission, the virulence of parasite and host characteristics like age or genetic make-up. Although admitted nowadays, the involvement of host genetic factors remains unclear. Discordant results exist, even concerning the best-known malaria resistance genes that determine the structure or function of red blood cells. Here we report on a genome-wide linkage and associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 79 publications
2
24
0
1
Order By: Relevance
“…Asymptomatic parasite density was also linked to chromosome 5q31 in a study from Senegal [126]. A genomewide linkage study revealed three strongly suggestive lines of evidence for linkage between mild malaria attacking both the 6p25.1 and the 12q22 regions and between the 20p11q11 region and the prevalence of parasite density in asymptomatic Senegalese children [127]. Furthermore, in this study, one gene associated with malaria infection in the 5q31–q33 was also detected, confirming the importance of this genetic region in the susceptibility to malaria infection [127].…”
Section: Immune Responsementioning
confidence: 99%
“…Asymptomatic parasite density was also linked to chromosome 5q31 in a study from Senegal [126]. A genomewide linkage study revealed three strongly suggestive lines of evidence for linkage between mild malaria attacking both the 6p25.1 and the 12q22 regions and between the 20p11q11 region and the prevalence of parasite density in asymptomatic Senegalese children [127]. Furthermore, in this study, one gene associated with malaria infection in the 5q31–q33 was also detected, confirming the importance of this genetic region in the susceptibility to malaria infection [127].…”
Section: Immune Responsementioning
confidence: 99%
“…It should be stressed, however, that we did not found linkage of IgG levels to chromosome 5q31-q33, which contains numerous genes encoding cytokines, and which was linked to parasitaemia. 3,4,[25][26][27][28] Thus, it seems that genetic variation within IL4, IL5 and IL13 genes located within chromosome 5q31-q33 does not markedly alter the levels of IgG and IgG subclasses against P. falciparum antigens in our study population, although those genes are known to be involved in antibody production, and although IL4 polymorphism was associated to antimalarial IgG levels. 21 In the same way, we did not find, in the chromosomal regions linked to IgG phenotypes, any genes encoding the cytokines known to be involved in isotype switching or B cell proliferation and differentiation, such as IL6, IL10 or IFNγ.…”
Section: Discussionmentioning
confidence: 58%
“…2,22 In other populations, ABO blood group genes located within chromosome 9q34 were associated with parasitemia and severe malaria, 23,24 whereas chromosome 12q22 was linked to mild malaria in a Senegalese population. 3 Because the antibody levels may depend on the exposure to parasite antigens, we further assessed the linkage of IgG and IgG subclass levels to the chromosomal regions of interest when taking into account parasitemia; the analyses yielded very similar results, ruling out the possibility of false linkage results due to this confounding factor. All together, these results suggest that some loci controlling the production of IgG or IgG subclasses may control parasitemia or mild malaria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…to determine the incidence or prevalence of clinical malaria in an area or in a population under close medical surveillance) clinical malaria is often considered as any case of fever or fever-related symptoms (headache, vomiting, subjective sensation of fever) associated with a P. falciparum parasite/leukocyte ratio higher than an age-dependent pyrogenic threshold of PD previously identified in the patient [43], [44]. In this case, a feverish individual harboring a PD under his age-specific threshold is not considered as a malaria case and will be monitored by the medical team involved in the study.…”
Section: Discussionmentioning
confidence: 99%